The Effect of Video on The Level of Knowledge of Adolescent Females About Breast Self-Examination at SMA Negeri 1 Ubud - Lisnawati, Ketut; Pintari, Ni Wayan Fira; Sintari, Silvia Ni Nyoman (Future Science, 2025)
Introduction: Breast cancer is one of the causes of death in women in the world, caused by the lack of knowledge among women in detecting early signs of breast cancer. Breast self-examination (BSE) is one way that can be done to detect early abnormalities in the breast to prevent breast cancer. Objective: The purpose of this study was to determine the effect of audiovisual videos on the level of knowledge of female adolescents about BSE. Methods: The research used a quasi-experiment with a pre-post-test nonequivalent control group design. The population in the study was all female students at SMA Negeri 1 Ubud, totaling 584 students. A research sampling technique using purposive sampling and the dropout formula comprised 17 respondents for each treatment and control group. Results: The results of the study using the Independent Sample t-test on the knowledge score of BSE after being given an audiovisual video in the treatment and control groups obtained p = 0.000 <0.05, indicating that there was an effect of audiovisual videos on the level of knowledge of adolescent girls about BSE. Conclusion: It is recommended that adolescent girls apply the method of early detection of breast cancer by doing BSE regularly. It would help to prevent breast cancer.